Perbandingan Sistem Manajemen Mutu ISO 9001:2008, Standard BANPT dan Total Quality Management di UIN Maulana Malik Ibrahim Malang - Asy’ari, Hasyim; Hasyim Asy’ari (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
Implementation of ISO Quality Management System (QMS) at UIN Maulana Malik Ibrahim (Maliki) Malang shows the spirit of the modernization of the campus management system. Application of ISO QMS is intended to facilitate the leaders of the campus to meet the standard of BAN-PT while building TQM. This research is focused on the comparative analysis of the implementation of ISO QMS, the role of Standard of BANPT, and the application of TQM in UIN Maliki Malang. The approach used is qualitative research, with data collection techniques such as interviews, observation, and document study. This research finds that, among others, UIN’s leaders and internal stakeholders have sought to implement the clauses of ISO QMS correctly and consistently; and increase the involvement of academicians in sustainable campus quality improvement efforts. Implementation of QMS ISO becomes a medium to fulfill the Standard of BANPT as well as the foundation for the implementation of TQM.